Rights for the nazis, communists and ku klux klan: An empirical analysis of student perceptions - Vogel, Ronald E. (American journal of criminal justice, 1984)
This article presents an empirical study which examines the willingness of students on a Southern campus to extend First Amendment rights to members of the Communist Workers Party, the American Nazi Party, and the Ku Klux Klan. The rights under study include the freedom of the press, freedom of speach, freedom to assemble and march, and freedom to run for public office. The rights were first examined as abstract principles available to everyone, and then as rights available to groups whose philosophies the students might oppose. A variety of situations were examined on a 68-item questionnaire.